Mitigation of Potential Hazard Sources in the Ship's Engine Room within the Maritime Industry Using the Hazard and Operability Study (HAZOP) and Fault Tree Analysis (FTA) Methods: A Case Study of XYZ Ship - Daryanto, Daryanto; Kuncowati, Kuncowati (Universitas Hang Tuah, 2025)
The development of the maritime industry demands improved work safety, especially in high-risk areas such as a ship's Engine Room. This study aims to identify potential hazards in the Engine Room of ship XYZ using the Hazard and Operability Study (HAZOP) and Fault Tree Analysis (FTA) methods. The results indicate the presence of several hazards with varying risk levels. The analysis identified 15 hazard sources, with 3 classified as high risk, 5 as medium risk, and 7 as low risk. Through FTA, the primary causes of potential accidents were identified, and mitigation measures were recommended, including design improvements, enhanced maintenance systems, and safety training for the ship’s crew.